Awareness of folklore in multimedia: spoken discourse among learners - Abd Rahim, Normaliza; Abdul Halim, Hazlina; Mamat, Roslina (DRUNPP Sarajevo, 2014)
This study focuses on the spoken discourse among primary school learners. The objectives of the study were to identify and discuss the multimedia components of the program used in order to give awareness towards the Malay folklore. The samples of the study consist of 10 subjects from a school in Melaka. The subjects were given a Malay folklore program. They viewed the program and they were divided into two groups. The groups were given two hours a week for four weeks to discuss the multimedia elements of the program. The interactions were taped and analyzed by using the spoken discourse analysis by Stubbs (1983). The results of the study revealed that the subjects were able to give their views and opinions based on the layout of the Malay folklore program. It is hoped that further study will focus on other component of multimedia in other genre of Malay literature.